More than rural : textures of Thailand's agrarian transformation - Rigg, Jonathan, 1959- (University of Hawaiʻi Press, 2019)
In the 1970s, Thailand was developing but poor and largely agrarian. By the 1980s it had become the fastest growing large economy in the world and, in the process, made the transformation from a low-income to a middle-income economy. Fast forward to 2010 and Thailand had climbed yet another rung in the development ladder to become, according to World Bank criteria, an upper middle-income economy. Throughout this period of economic and social transformation, contrary to historical experience and theoretical models, one thing has remained constant: the central role of Thai smallholder farming. This conundrum--the persistence of the smallholder in a time of extraordinary change--lies at the heart of this book. In More than Rural author Jonathan Rigg explores how people in the countryside have adapted to their changing world, the new opportunities available, and the consequences for rural life and living. The Thai government has successfully "developed" the countryside, but with unexpected results. New household forms have emerged, women have become mobile in a manner few expected, and relations between rural and urban have changed. Yet the smallholder has persisted, and Rigg's attempts to understand why offer a fresh perspective on Thailand's development. Setting aside the urban, industrial point of view that we so often privilege, Rigg asks different questions about Thailand's development. What if, he wonders, the present changes are not simply way stations, transitions to the main act of urbanization? What if they represent a new form of rural livelihood?Rigg's thoughtful, nuanced approach to agrarian change--viewing the countryside as more than agriculture, the rural as more than the countryside, and rural people as more than farmers--offers insights into Thailand's wider transformations (class identities, intergenerational relations), its political impasse, and more. Based on over three-and-a-half decades of fieldwork in seventeen villages, across three regions, and encompassing more than one thousand households, and a deep knowledge of primary and published sources, More than Rural is a significant work with implications for contemporary development across Asia and the global South